Numerical Solution of the Modified Equal Width Wave Equation - Seydi Battal Gazi Karakoç; Turabi Geyikli (International Journal of Differential Equations)
Numerical solution of the modified equal width wave equation is obtained by using lumped Galerkin method based on cubic B-spline finite element method. Solitary wave motion and interaction of two solitary waves are studied using the proposed method. Accuracy of the proposed method is discussed by computing the numerical conserved laws 𝐿2 and 𝐿∞ error norms. The numerical results are found in good agreement with exact solution. A linear stability analysis of the scheme is also investigated.